Indonesian government crisis communication facing coronavirus pandemic - Masduki, Anang; Niu, Panqiang; Yana, Maria Effi (International Journal of Communication and Society, 2022)
Many Indonesian officials have joked about the coronavirus outbreak. The Indonesian government has come to a point, namely crisis communication. With qualitative descriptive research, with data sources from scientific journals, articles from experts and intellectuals related to coronavirus, mass media news, and other relevant information. Analysis using triangulation techniques. This paper aims to reveal the communication side of the government's crisis and see society's reality in responding to information conveyed by Indonesian government agencies. As a result, the communication crisis that occurred was preceded by weak government coordination in dealing with the outbreak. Then the result is policymaking that is not correctly aligned and integrated. The government's various information to the public is also different and changing, confusing the community. On the other hand, people through social media convey a lot of information that has not been verified. So that it adds to the complexity of the problem of handling the coronavirus outbreak. In conclusion, informing and providing guidance for the community to deal with pandemics is the key to successful communication during a crisis.